2017
DOI: 10.7554/elife.23961
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear export receptor CRM1 recognizes diverse conformations in nuclear export signals

Abstract: Nuclear export receptor CRM1 binds highly variable nuclear export signals (NESs) in hundreds of different cargoes. Previously we have shown that CRM1 binds NESs in both polypeptide orientations (Fung et al., 2015). Here, we show crystal structures of CRM1 bound to eight additional NESs which reveal diverse conformations that range from loop-like to all-helix, which occupy different extents of the invariant NES-binding groove. Analysis of all NES structures show 5-6 distinct backbone conformations where the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(122 citation statements)
references
References 51 publications
10
108
4
Order By: Relevance
“…This suggested that subcellular localization of CHMP7 could be a key determinant to position CHMP4B foci. The CHMP7 Cterminal motif previously annotated as a MIM1 motif 2,21 closely resembles a type 1a highaffinity nuclear export signal (NES) 22 (Fig. 1c), suggesting a mechanism to exclude this 45kDa protein from the nucleus 23 .…”
mentioning
confidence: 89%
“…This suggested that subcellular localization of CHMP7 could be a key determinant to position CHMP4B foci. The CHMP7 Cterminal motif previously annotated as a MIM1 motif 2,21 closely resembles a type 1a highaffinity nuclear export signal (NES) 22 (Fig. 1c), suggesting a mechanism to exclude this 45kDa protein from the nucleus 23 .…”
mentioning
confidence: 89%
“…Hundreds of different amino acid sequences have been experimentally validated as bona-fide NESs that bind the receptor with different affinity, and may be exported with different efficiency [33,42,43] . This high variability can be explained by the recent finding that NESs with differ-ent backbone conformations can bind the receptor, and that not all export signals occupy the XPO1 NESbinding groove to the same extent [44] .…”
Section: Xpo1-mediated Protein Nuclear Export: Cargos Mechanisms Andmentioning
confidence: 99%
“…We hypothesize that the Mto1 NES-M may be a natural high-affinity NES. In recent years, the NES “consensus” has evolved in concert with new experimental findings (Dong et al, 2009, Fung et al, 2015, Fung et al, 2017, Guttler et al, 2010, Monecke et al, 2009). In particular, relative to an original consensus involving four spaced hydrophobic residues (Kutay & Guttinger, 2005), several high-affinity NESs depend on a fifth hydrophobic residue, which may also be present in the Mto1 NES-M (Fig.…”
Section: Discussionmentioning
confidence: 99%